Analisis Konvergensi dan Divergensi Komunikasi Antarbudaya: Studi Kasus Komunikasi Mahasiswa Papua di Universitas Mataram - Wahyu Prama Pratama Hpar; Wawan Kurniawan; Triya Rezeki Umais; Nindi Aulia Rahman; Jamilatul Islamiah; Wika Wahyuni (Dinasti Research, 2024)
Intercultural communication issues often pose challenges in higher education environments, especially in universities with diverse students from various cultural backgrounds. The University of Mataram, as one of Indonesia's higher education institutions, has a number of students from Papua who face difficulties in adapting to the local culture. This study aims to analyze the convergence and divergence in intercultural communication between Papua students and other students, particularly local students, at the University of Mataram, and to identify the factors influencing their adaptation and integration processes. The findings of this study reveal that Papua students encounter several challenges in communicating and adapting to the local culture at the University of Mataram. Key factors influencing the convergence and divergence in communication include language differences, social norms, and cultural practices. On the other hand, there are also some adaptation mechanisms utilized by Papua students to overcome these challenges, such as forming support groups and participating in local cultural activities